The effectiveness of using a tracker chart to enhance willingness to communicate among ESL learners in a philosophical inquiry classroom discussion - Ismail, Lilliati; Abd Rahman, Fadzilah; Othman, Moomala; Ahmad, Noorlila (Universiti Putra Malaysia Press, 2020)
There has been burgeoning interest among researchers in investigating Willingness to Communicate (WTC) as part of the instructional method in a Philosophical Inquiry (PI) Discussion. The present study investigated the effectiveness of using a tracker chart in a PI classroom discussion to promote WTC. The participants were 30 undergraduate students in a public university in Malaysia. A WTC questionnaire was administered before and after the intervention. A tracker chart was used to gauge the number of learner responses that occurred throughout the 8-week intervention. Interview sessions with seven randomly selected participants were then carried out to gauge the learners’ perceptions of using the tracker chart in PI Discussions and its effects on their WTC. The data analysis showed that the tracker chart resulted in increments in the number of responses throughout the 8 weeks, and participants reported that the tracker chart had positive effects on their WTC as they were more conscious of their responses and contributions in the PI Discussions. The t-test result also showed a significant difference in the participants’ levels of WTC which indicates that the use of the tracker chart in PI Discussions helped increase the participants’ WTC. The results indicate that the use of a tracker chart could have positive effects in enhancing learners’ WTC in PI Discussions.